Geophysical study of the probable burial site of Hetman Vyhovsky - Sapuzhak, O.Ya.; Syroiezhko, O.V.; Chobotok, I.O.; Kolyadenko, V.V.; Maryash, I.M.; Yarema, I.I. (Geofizicheskiy Zhurnal, 2025)
According to historical sources, the burial of Hetman Vyhovsky may be located in the village of Ruda, Stryi district, Lviv region. Before conducting archaeological excavations at the probable site of its location, near a church, it was necessary to identify promising sites for this place. For this purpose, a complex of geophysical studies using magnetic reconnaissance and ground-penetrating radar sounding methods was applied. Anomalous zones in the magnetic field were detected. Also, ground-penetrating radar sounding recorded local inhomogeneities, mainly located in zones of magnetic anomalies. The nature of the discovered objects indicates that they may be the target archaeological objects, namely, ancient burials and underground remains of structures.